EMBRACING CONTEMPORARY COLORS OF ENDANGERED ENDEMIC BIRDS IN LURIK WEAVING FOR THE PRESERVATION OF INDONESIAN CULTURAL HERITAGE - Wulandari, Sari (jfpublisher, 2023)
Traditional weaving in Yogyakarta might become an extinction, as many of the young weavers are turning into sand miners or factory laborers due to lack of regeneration. Therefore, Lawe offers a new interpretation of lurik through appropriate stories to attract young people to use it as part of their fashion. This research is concerned on Lawe’s efforts in producing modern lurik weaving that has a message for young people and to encourage an understanding of the importance of lurik as a traditional Indonesian woven textile. Using the colors and patterns from their collection, Lawe took this opportunity to tell stories about Indonesia’s environment, especially the endangered native birds in Indonesia. The researchers used qualitative research methods and interdisciplinary strategies with Visual Communication Design and Cultural Studies to generate scientific knowledge. The research findings identified that in generating patterns, the composition of lines in lurik weaving is affected by the color ratio of bird feathers. This research contributes to inspiring the creative economy in cultural value and pride in one’s work for years to come, and the sustainable preservation of the Indonesian natural environment and cultural heritage.